1992
DOI: 10.1055/s-0038-1648509
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin Levels in Patients with Malignancy

Abstract: SummaryThrombospondin (TSP), a large glycoprotein present in platelets, and various normal and tumor tissues, has recently been shown to promote cell adhesion and platelet aggregation. Most importantly because TSP has been shown to promote metastasis of melanoma tumor cells to the lung in a murine model (1) and since thromboembolic events commonly occur in patients afflicted with metastatic tumors, we explored the role of TSP in human cancer by measuring TSP blood levels in patients with various malignant neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 10 publications
6
32
1
2
Order By: Relevance
“…TSP-1 that is present in the tumor microenvironment also acts to suppress tumor cell growth through activation of transforming growth factor ␤ in those tumor cells that are responsive to TGF-␤ (55). TSP-1 has been shown to be highly expressed in human malignant tissues and present in higher than normal levels in the plasma of cancer patients (56), like beast, lung, and colorectal carcinoma (57), which is in contrast with our result, suggesting a possible unique figure of hepatocellular carcinoma.…”
Section: Resultscontrasting
confidence: 99%
“…TSP-1 that is present in the tumor microenvironment also acts to suppress tumor cell growth through activation of transforming growth factor ␤ in those tumor cells that are responsive to TGF-␤ (55). TSP-1 has been shown to be highly expressed in human malignant tissues and present in higher than normal levels in the plasma of cancer patients (56), like beast, lung, and colorectal carcinoma (57), which is in contrast with our result, suggesting a possible unique figure of hepatocellular carcinoma.…”
Section: Resultscontrasting
confidence: 99%
“…Ductal cancers express THBS-1 mainly in the surrounding stroma, while in lobular tumors it is present in the more invasive tumor cells (33). In accordance with these observations, Tuszynski et al and Byrne et al found higher blood levels of THBS-1 protein in breast cancer patients compared to healthy controls (34,35), while the present study showed that blood THBS-1 mRNA levels are also elevated. Thrombospondins are secreted in blood by platelets and monocytes (36).…”
Section: Patients ---------------------------------------------------supporting
confidence: 90%
“…A correlation between the plasma thrombosponies 38 and antithrombospondin antibodies 39 have been shown to prevent the development of metastasis in din levels and the stage of colorectal carcinoma was observed. Because the plasma thrombospondin level the murine model.…”
Section: Comparison Of the Plasma Thrombospondin Level Between Patienmentioning
confidence: 90%